Party alignment and political budget cycles: The Argentine provinces - Daniel Lema; Jorge M. Streb (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2013)
The links between subnational political budget cycles (PBCs) and the national government in federal countries have seldom been studied. We study the behavior of the budget balance, public expenditures, and revenues in Argentine provinces during the 1985-2001 period. We find that in election years public expenditures increase, but revenues also do - a result exactly contrary to the predictions of rational opportunistic models of aggregate PBCs - and the budget deficit does not increase significantly. Since the increase in provincial revenues is due to larger federal transfers, we incorporate the influence of party alignment between governors and president. Public expenditures in election years increase in aligned provinces because of larger federal transfers, without affecting the budget deficit; in contrast, the budget deficit tends to increase in unaligned provinces. The federal government thus plays a key role in subnational PBCs, with an electoral cycle in the allocation of federal transfers.
Keywords: D72; E62; 330; political budget cycles; federal countries; discretional transfers; tactical allocation; party alignment; distributive politics